Comparative Analysis of IPV6 And IPV4 Protocols - Solano Benítez, Ingrid Paola; Méndez, Guefry Agredo; Agredo Salazar, Nilsa Milena; Cabezas Burbano, Danyeli; Uribe Guirales, Carlos Iván (Ingeniería Solidaria, 2010)
The technological trend glimpses a forced change towards an IP v6 platform, due to, among other reasons, the Internet spread as a daily tool, the emergence of new technologies and the use of applications that require higher system performance. As a response to the pointed trend, at the Program of Systems Engineering from the Faculty of Engineering, at The “Universidad Cooperativa de Colombia” –Popayán Satellite Campus, a graduation work to implement this platform was prepared. The article explains the proposal in detail and presents the methodology elaborated, the results obtained and the analysis and interpretation of those.